Mittlere Schwingungsamplituden von ReOF4 und ReOF5 - Baran, Enrique José (1978)
Mean amplitudes of vibration for ReOF4 and ReOF5 have been calculated from spectroscopic data in the temperature range between 0 and 1,000 K. The results are briefly discussed, some comparisons are made with structurally related species and certain aspects of the bond properties are analyzed.